On the nursery-web spider genus Hypsithylla Simon, 1903 (Araneae: Pisauridae) and its synonymy with Hygropoda Thorell, 1894 - Da Silva, Estevam L. Cruz (Zootaxa, 2012)
The spider genus Hypsithylla was proposed by Simon (1903) and comprises only two species (Platnick, 2012). The type-species, Hypsithylla linearis Simon, 1903, is based on an immature female and Hypsithylla celebesiana Strand, 1913, is known from a single female from Sulawesi.